High-strength and high-toughness titanium alloy and heat treatment method and preparation method thereof

By adjusting the element content in titanium alloy and adopting multi-stage heat treatment methods, the problem of insufficient strength and toughness of titanium alloy in the operating mechanism rod of the tank circuit breaker is solved, and a high-strength, high-toughness and lightweight titanium alloy material is realized, meeting the high mechanical load and fast action requirements of the tank circuit breaker.

CN119614941APending Publication Date: 2025-03-14CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411601455.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing titanium alloy materials are insufficient in strength and toughness in the tank circuit breaker operating mechanism rod, which cannot meet the requirements of high mechanical loads and rapid action.

Method used

A high-strength and high-toughness titanium alloy is adopted, with an element content of Al: 5.0-5.6%, Mo: 4.5-5.2%, V: 4.8-5.5%, Cr+Fe: 2.8-3.5%, and the balance is Ti. Through a multi-stage heat treatment method, including first-stage, second-stage, third-stage and fourth-stage heat treatment steps, the microstructure of the titanium alloy is adjusted to improve its strength and toughness.

Benefits of technology

The tensile strength of titanium alloy is ≥1300MPa, elongation ≥5% and impact toughness ≥500kJ/m2, which meets the high strength and high toughness requirements of the tank circuit breaker operating mechanism rod, and improves the comprehensive mechanical properties of the material under lightweight conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614941A_ABST
    Figure CN119614941A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength and high-toughness titanium alloy as well as a heat treatment method and a preparation method thereof, and the high-strength and high-toughness titanium alloy comprises the following elements in percentage by weight: 5.0-5.6% of Al; 4.5 to 5.2 percent of Mo; v: 4.8 to 5.5%; 2.8%-3.5% of Cr and Fe; and the balance of Ti. The preparation method comprises the steps that weighed titanium alloy raw materials are subjected to powder mixing, pre-diffusion, cold pressing blank making, vacuum sintering and multi-stage heat treatment, and the multi-stage heat treatment process comprises the steps that a sintered titanium alloy blank is put into a furnace at the temperature of 20-60 DEG C below the phase transformation point, heat preservation is conducted for 1-2 h, and then water cooling is conducted to the room temperature; then putting into a furnace at the temperature of 780-880 DEG C, preserving heat for 2-3 hours, and then water-cooling to room temperature; then, feeding into a furnace at the temperature of 710-770 DEG C, preserving heat for 1-2 hours, and then air-cooling to room temperature; and finally, feeding into a furnace at the temperature of 650-710 DEG C, preserving heat for 2-4 hours, and then air-cooling to room temperature to obtain the high-strength and high-toughness titanium alloy. The high-strength and high-toughness titanium alloy comprises a primary alpha phase, a grain boundary discontinuous alpha phase, a secondary alpha phase and a residual beta phase, and the strength and toughness are remarkably improved while the lightweight requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and specifically relates to a high-strength and high-toughness titanium alloy and a heat treatment method and a preparation method thereof. Background Art

[0002] Tank circuit breakers are used to quickly cut off faults, effectively control and protect important equipment in power plants and substations, and power transmission and transformation lines, and prevent major accidents. Tank circuit breakers themselves need to have high reliability in terms of electrification, but the operating mechanism of the tank circuit breaker mechanism is subjected to a large peak force in a short period of time during the driving process, which brings a huge mechanical load to the transmission structure (piston rod and sealing rod, etc.). Therefore, under the condition of reducing the motion mass and ensuring the rapidity of the action, high requirements are placed on the strength and mechanical reliability of the operating transmission structure.

[0003] At present, the material used for the operating mechanism rod is 35CrMo alloy structural steel, which has high static strength, impact toughness, high fatigue limit and hardenability, high creep strength and endurance strength at high temperature, no overheating tendency, small quenching deformation, and can be used to make important parts in various machines that need to withstand impact, bending and torsion, and high loads. However, 35CrMo alloy structural steel has a large mass, and the operating work required during the circuit breaker operation is large. The huge mechanical load reduces the stability of the entire mechanism and poses a challenge to the accuracy of phase selection and closing.

[0004] Titanium alloy has great advantages in lightweighting due to its high specific strength and high specific modulus. Compared with steel, the density of titanium alloy is about 60% of that of steel. According to the service conditions of the tank circuit breaker operating mechanism rod, it is necessary to develop a tensile strength ≥1300Mpa, elongation ≥5%, and impact toughness ≥500kJ / m 2 At present, the strength of some types of titanium alloys has reached more than 1000MPa, but it still cannot meet the requirements of the tank type circuit breaker operating mechanism rod. Therefore, it is urgent to develop titanium alloy materials that meet the requirements, with high strength and high toughness. Summary of the invention

[0005] In view of the problem that the operating mechanism of the tank type circuit breaker requires a material with high strength, high toughness and light weight, the present invention solves the defects of low strength and low toughness of existing titanium alloy materials and provides a high-strength and high-toughness titanium alloy and a heat treatment method and a preparation method thereof.

[0006] The purpose of the present invention is to adopt the following technical solutions to achieve:

[0007] A high-strength and high-toughness titanium alloy, wherein the content of each element by weight percentage is: Al: 5.0-5.6%; Mo: 4.5-5.2%; V: 4.8-5.5%; Cr+Fe: 2.8-3.5%; and the balance is Ti.

[0008] The present invention also provides a high-strength and high-toughness titanium alloy heat treatment method, which is used in the heat treatment process of the high-strength and high-toughness titanium alloy after sintering, comprising the following steps:

[0009] The sintered titanium alloy blank is placed in a furnace at a temperature of 20 to 60°C below its phase transition point and kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a first-grade heat-treated titanium alloy;

[0010] The primary heat-treated titanium alloy is placed in a furnace at a temperature of 780 to 880° C. and kept warm for 2 to 3 hours, and then water-cooled to room temperature to obtain a secondary heat-treated titanium alloy;

[0011] The secondary heat-treated titanium alloy is placed in a furnace at a temperature of 710-770° C. and kept warm for 1-2 hours, and then air-cooled to room temperature to obtain a tertiary heat-treated titanium alloy;

[0012] The three-stage heat-treated titanium alloy is placed in a furnace at a temperature of 650-710° C. and kept warm for 2-4 hours, and then air-cooled to room temperature to obtain the high-strength and high-toughness titanium alloy.

[0013] Preferably, the heat treatment method comprises the following steps:

[0014] The sintered titanium alloy blank is placed in a furnace at a temperature 30 to 50°C below its phase transition point and kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a first-grade heat-treated titanium alloy;

[0015] The primary heat-treated titanium alloy is placed in a furnace at a temperature of 800 to 850° C. and kept warm for 2 to 3 hours, and then water-cooled to room temperature to obtain a secondary heat-treated titanium alloy;

[0016] Putting the secondary heat-treated titanium alloy into a furnace at a temperature of 720-750° C. and keeping it for 1-2 hours, and then air-cooling it to room temperature to obtain a tertiary heat-treated titanium alloy;

[0017] The three-stage heat-treated titanium alloy is placed in a furnace at a temperature of 680-700° C. and kept warm for 2-4 hours, and then air-cooled to room temperature to obtain the high-strength and high-toughness titanium alloy.

[0018] Preferably, the phase transition point ranges from 980 to 990°C.

[0019] Preferably, the sintered titanium alloy blank is placed in a furnace at a temperature 40° C. below its phase transition point, kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a primary heat-treated titanium alloy.

[0020] Based on the same inventive concept, the present invention also provides a method for preparing a high-strength and high-toughness titanium alloy, which is used to prepare the high-strength and high-toughness titanium alloy, including the high-strength and high-toughness titanium alloy heat treatment method.

[0021] Preferably, the preparation method further comprises the following steps before implementing the high-strength and high-toughness titanium alloy heat treatment method:

[0022] Powder mixing: weighing titanium alloy raw materials according to the mass ratio, mixing the titanium alloy raw materials and then drying them to obtain dried titanium alloy raw materials;

[0023] Pre-diffusion: placing the dried titanium alloy raw material in a vacuum environment for pre-diffusion to obtain a pre-diffused titanium alloy raw material;

[0024] Cold pressing a blank: cold pressing the pre-diffused titanium alloy raw material into a blank to obtain a titanium alloy blank;

[0025] Vacuum sintering: sintering the titanium alloy blank in a vacuum environment to obtain a sintered titanium alloy blank.

[0026] Preferably, the powder mixing specifically includes: weighing titanium alloy raw materials according to the mass ratio, using a three-dimensional motion powder mixer to fully mix the titanium alloy raw materials for 1 to 2 hours, and then placing them in a vacuum oven at 140 to 160° C. and drying them for 3 to 5 hours to obtain a dried titanium alloy raw material.

[0027] Preferably, the pre-diffusion specifically includes: placing the dried titanium alloy raw material in a vacuum of 1×10 -3 In a vacuum environment below Pa, pre-diffusion is carried out at 700-750° C. for 20-30 minutes to obtain a pre-diffused titanium alloy raw material.

[0028] Preferably, the cold pressing of the blank specifically comprises: cold pressing the pre-diffused titanium alloy raw material at a pressure of 240-260 MPa for 8-15 minutes to obtain a titanium alloy blank.

[0029] Preferably, the vacuum sintering specifically comprises: sintering the titanium alloy blank in a vacuum environment with a vacuum degree of 1×10 -3 Pa, the temperature is 1150-1250°C, the sintering time is 3-6h, and the heating rate is 5-20°C / min to obtain a sintered titanium alloy blank.

[0030] Preferably, the titanium alloy raw material is prepared by rotary electrode atomization and has a particle size of 100 to 325 meshes.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The high-strength and high-toughness titanium alloy of the present invention has the following elements in weight percentage: Al: 5.0-5.6%; Mo: 4.5-5.2%; V: 4.8-5.5%; Cr+Fe: 2.8-3.5%; the balance is Ti. The titanium alloy of the present invention has high strength and excellent toughness while meeting the requirements of lightweight.

[0033] The high-strength and high-toughness titanium alloy heat treatment method of the present invention comprises the following steps: placing a sintered titanium alloy blank into a furnace at a temperature of 20 to 60°C below its phase transformation point and keeping it warm for 1 to 2 hours, and then water cooling it to room temperature to obtain a first-stage heat-treated titanium alloy; placing the first-stage heat-treated titanium alloy into a furnace at a temperature of 780 to 880°C and keeping it warm for 2 to 3 hours, and then water cooling it to room temperature to obtain a second-stage heat-treated titanium alloy; placing the second-stage heat-treated titanium alloy into a furnace at a temperature of 710 to 770°C and keeping it warm for 1 to 2 hours, and then air cooling it to room temperature to obtain a third-stage heat-treated titanium alloy; placing the third-stage heat-treated titanium alloy into a furnace at a temperature of 650 to 710°C and keeping it warm for 2 to 4 hours, and then air cooling it to room temperature to obtain the high-strength and high-toughness titanium alloy. During the first-stage heat treatment, the primary α phase precipitates, but the time is short, the α phase does not have time to fully grow, the grain boundary α is discontinuous, and the β phase is transformed into martensite after water cooling; during the second-stage heat treatment, the martensite decomposes, the secondary α phase precipitates, and the generated secondary α phase is smaller in size, which plays a role of dispersion strengthening, and the primary α phase is spheroidized; the temperature of the third-stage heat treatment is lower than the temperature of the second-stage heat treatment, which can prevent the rapid growth of the primary and secondary α phases; the fourth-stage heat treatment process can adjust the α phase distribution, make the α phase distribution more dispersed, and reduce the width of the grain boundary non-precipitation zone. At this time, if the temperature is lower than 550°C, a brittle ω phase will be formed, affecting the plasticity and toughness of the alloy; the microstructure of the titanium alloy blank after vacuum sintering is as follows Figure 1 , Figure 2 As shown by Figure 2 It can be seen that the sample is kept at high temperature for a long time during the sintering process, and the formed structure is mainly composed of coarse α phase and secondary α phase. The thickness of the coarse primary α phase exceeds 2μm, and the grain boundary α phase is continuously distributed. The coarse primary α phase and the continuous grain boundary α phase will have an adverse effect on the plasticity and toughness of the alloy, so special multi-stage heat treatment is required. The microstructure of the titanium alloy after four-stage heat treatment is shown in Figure 2. Figure 3 As shown in Figure 2, it can be seen that the grain boundary α phase (GBα phase) is obviously distributed discontinuously, which is consistent with Figure 2 Compared with the structure without multi-stage heat treatment, the grain boundary α phase is no longer continuous, the thickness of the primary α phase does not exceed 0.5μm, and the size is much smaller than the primary α phase formed after high-temperature sintering. The dispersed α phase contributes to the strength and toughness of the alloy, and improves the comprehensive mechanical properties of the material. The phase composition of the high-strength and high-toughness titanium alloy obtained by the multi-stage heat treatment method of the present invention includes primary α phase, discontinuous α phase at the grain boundary, secondary α phase and residual β phase. The primary α phase, discontinuous α phase at the grain boundary and secondary α phase have high strength and hardness. The appropriate amount of residual β phase can improve the plasticity and toughness of the titanium alloy, so that the strength and toughness of the titanium alloy material are significantly improved.

[0034] The high-strength and high-toughness titanium alloy preparation method of the present invention uses the powders of each element prepared by rotating electrode atomization as raw materials, uses a three-dimensional motion powder mixer to fully mix the powders, pre-diffuses them in a vacuum environment after drying to promote diffusion and adhesion between powder particles, then cold presses the blanks, and then sinters them into defect-free bulk titanium alloy materials by a vacuum sintering method, and finally uses a multi-stage heat treatment method to further improve the performance, so as to obtain a high-strength and high-toughness titanium alloy material with a tensile strength of ≥1300MPa, an elongation of ≥5%, and an impact toughness of ≥500kJ / m 2 It can replace high-density alloys such as steel in service environments subject to impact conditions, thereby achieving the purpose of lightweight components. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The microstructure diagram of the titanium alloy blank after vacuum sintering of the present invention;

[0036] Figure 2 This is an enlarged microstructure diagram of the titanium alloy blank after vacuum sintering of the present invention;

[0037] Figure 3 The microstructure diagram of the titanium alloy after the four-stage heat treatment of the present invention;

[0038] Figure 4 This is the microstructure diagram of the titanium alloy of Comparative Example 1. DETAILED DESCRIPTION

[0039] The present invention has conducted a large number of comparative experiments by adjusting the above parameters. The present invention is further described by citing some embodiments below. These embodiments are used to illustrate the present invention, rather than to limit the present invention. Any improvement to the process of the present invention under the premise of the present invention belongs to the scope of protection of the present invention.

[0040] Example 1

[0041] The high-strength and high-toughness titanium alloy material of this embodiment is prepared as follows:

[0042] Mixing powder: preparing titanium alloy raw material with Ti-5Al-5Mo-5V-3Cr as nominal composition, wherein the content of each element by weight percentage is: Al: 5.0%; Mo: 5.0%; V: 5.0%; Cr: 3.0%; the balance is Ti (particle size 100-325 mesh), putting the titanium alloy raw material into a three-dimensional motion powder mixer for thorough mixing for 1.5 hours, and then putting it into a vacuum oven for drying at 150° C. for 3 hours to obtain a dried titanium alloy raw material;

[0043] Pre-diffusion: The titanium alloy raw material dried in S1 is placed in a vacuum of 1×10 -3 In a vacuum environment below Pa, pre-diffusion is performed at 720°C for 25 minutes to obtain a pre-diffused titanium alloy raw material;

[0044] Cold pressing blank: cold pressing the titanium alloy raw material after pre-diffusion in S2 at a pressure of 240 MPa for 10 min to obtain a titanium alloy blank;

[0045] Vacuum sintering: The titanium alloy blank in S3 is sintered in a vacuum of 1×10 -3 Pa, sintering in a vacuum environment at a temperature of 1200°C, a heating rate of 10°C / min, and a holding time of 5h to obtain a sintered titanium alloy blank;

[0046] Multi-stage heat treatment: using differential scanning calorimetry to determine the phase transition point of the sintered titanium alloy blank is 980°C, the sintered titanium alloy blank is heated to 950°C, 30°C below the phase transition point, and then placed in a furnace for 1 hour and water-cooled to room temperature; then heated to 820°C and placed in a furnace for 2 hours and then water-cooled to room temperature; then heated to 750°C and placed in a furnace for 1 hour and then air-cooled to room temperature; finally heated to 680°C and placed in a furnace for 2 hours and then air-cooled to room temperature to obtain the high-strength and high-toughness titanium alloy.

[0047] Example 2-11

[0048] The high-strength and high-toughness titanium alloy material provided in Example 2-11 has a nominal composition and content of each element as shown in Table 1:

[0049] Table 1 Different raw material ratios

[0050]

[0051] Continued

[0052]

[0053]

[0054] The preparation method of the high-strength and high-toughness titanium alloy provided in Example 2-11 is the same as that in Example 1, except that the preparation conditions are different, as shown in Table 2:

[0055] Table 2 Differences in preparation conditions

[0056]

[0057]

[0058] Continued

[0059] parameter Example 7 Example 8 Example 9 Example 10 Embodiment 11 Mixing time (h) 1 1.5 2 1 1.5 Drying temperature (℃) 140 150 155 140 160 Baking time (h) 3.5 3 4 5 4 Pre-diffusion temperature(℃) 720 710 735 750 740 Pre-diffusion time (min) 20 25 25 20 30 Cold pressing billet pressure (MPa) 240 245 250 255 260 Cold pressing time (min) 10 12 13 8 15 Sintering temperature(℃) 1160 1200 1220 1240 1250 Sintering heating rate (℃ / min) 15 12 18 10 20 Sintering holding time (h) 3 4 4.5 5 6 Phase transition point(℃) 980 985 990 990 985 Below phase transition point(℃) 30 50 20 60 55 Primary heat treatment temperature (℃) 950 935 970 930 930 First stage heat treatment time (h) 1.5 2 2 1 1.5 Secondary heat treatment temperature (℃) 780 790 870 880 860 Secondary heat treatment time (h) 2.5 3 2 2.5 2.5 Third stage heat treatment temperature (℃) 710 770 750 760 745 Third stage heat treatment time (h) 1.5 2 2 1 1.5 Fourth stage heat treatment temperature (℃) 650 710 680 700 660 Four-stage heat treatment time (h) 3 3.5 3.5 4 2.5

[0060] Comparative Example 1

[0061] The titanium alloy provided in this comparative example has the same raw material ratio as that in Example 3, and the preparation method is the same as that in Example 3, except that only two-stage heat treatment is performed on the sintered titanium alloy blank:

[0062] Primary heat treatment: 30℃ below the phase change point, i.e. 955℃, put into the furnace and keep warm for 2h, then water cool;

[0063] Secondary heat treatment: then put the product into a furnace at 650°C and keep it there for 5 hours, then air cool it to obtain the titanium alloy.

[0064] Test Results

[0065] The tensile strength, elongation and impact toughness of the titanium alloy materials obtained in Examples 1-11 and Comparative Example 1 were tested. The test results are summarized in Table 3.

[0066] Table 3 Mechanical properties test results

[0067] Tensile strength(MPa) Elongation(%) <![CDATA[Impact toughness (kJ / m 2 )]]> Example 1 1339 7 523 Example 2 1328 8 518 Example 3 1318 6 509 Example 4 1314 7 513 Example 5 1305 8 515 Example 6 1302 7 507 Example 7 1310 6 503 Example 8 1312 8 510 Example 9 1315 6 512 Example 10 1303 7 508 Embodiment 11 1305 7 504 Comparative Example 1 1185 5 479

[0068] It can be seen from the test results of Examples 1-11 that the titanium alloy material prepared by the preparation method described in this application has significantly improved mechanical properties, with a tensile strength of ≥1300MPa, an elongation of ≥5%, and an impact toughness of ≥500kJ / m 2 According to the comparison between Example 3 and Comparative Example 1, the multi-stage heat treatment process described in the present application significantly improves the strength and toughness of the titanium alloy material. Further observation at the microscopic level, Figure 3 The microstructure of the high-strength and high-toughness titanium alloy obtained by the present invention shows that the α phase at the grain boundary is obviously distributed discontinuously. Figure 2 Compared with the microstructure without multi-stage heat treatment, the grain boundary α phase is no longer continuous, and the thickness of the primary α phase does not exceed 0.5 μm, which is much smaller than the primary α phase formed after high-temperature sintering. The dispersed α phase contributes to the strength and toughness of the alloy, and improves the comprehensive mechanical properties of the material. The α phase of the titanium alloy microstructure obtained by the present invention is more dispersed. The microstructure of the titanium alloy after sintering provided in Comparative Example 1 is as follows Figure 4 As shown in Figure 2, it can be observed that there is a continuous distribution of α phase at the grain boundary, and Figure 3 Compared with the sintered state ( Figure 1 and Figure 2 ) is significantly smaller than that of the α phase in the crystal, but larger than that observed in the example. The α phase distribution of the microstructure obtained by the four-stage heat treatment in the example is more dispersed. Due to the formation of a discontinuous grain boundary α phase and the dispersed distribution of a small-sized α phase in the crystal, the comprehensive performance of the example is better than that of the comparative example.

[0069] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.

Claims

1. A high-strength and high-toughness titanium alloy, characterized in that: The content of each element is calculated in weight percentage as follows: Al: 5.0-5.6%; Mo: 4.5-5.2%; V: 4.8-5.5%; Cr+Fe: 2.8-3.5%; and the balance is Ti.

2. A high-strength and high-toughness titanium alloy heat treatment method, characterized in that: The heat treatment process for a high-strength and high-toughness titanium alloy after sintering as claimed in claim 1 comprises the following steps: The sintered titanium alloy blank is placed in a furnace at a temperature of 20 to 60°C below its phase transition point and kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a first-grade heat-treated titanium alloy; The primary heat-treated titanium alloy is placed in a furnace at a temperature of 780 to 880° C. and kept warm for 2 to 3 hours, and then water-cooled to room temperature to obtain a secondary heat-treated titanium alloy; The secondary heat-treated titanium alloy is placed in a furnace at a temperature of 710-770° C. and kept warm for 1-2 hours, and then air-cooled to room temperature to obtain a tertiary heat-treated titanium alloy; The three-stage heat-treated titanium alloy is placed in a furnace at a temperature of 650-710° C. and kept warm for 2-4 hours, and then air-cooled to room temperature to obtain the high-strength and high-toughness titanium alloy.

3. The high-strength and high-toughness titanium alloy heat treatment method according to claim 2, characterized in that: The following steps are involved: The sintered titanium alloy blank is placed in a furnace at a temperature 30 to 50°C below its phase transition point and kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a first-grade heat-treated titanium alloy; The primary heat-treated titanium alloy is placed in a furnace at a temperature of 800 to 850° C. and kept warm for 2 to 3 hours, and then water-cooled to room temperature to obtain a secondary heat-treated titanium alloy; Putting the secondary heat-treated titanium alloy into a furnace at a temperature of 720-750° C. and keeping it for 1-2 hours, and then air-cooling it to room temperature to obtain a tertiary heat-treated titanium alloy; The three-stage heat-treated titanium alloy is placed in a furnace at a temperature of 680-700° C. and kept warm for 2-4 hours, and then air-cooled to room temperature to obtain the high-strength and high-toughness titanium alloy.

4. The high-strength and high-toughness titanium alloy heat treatment method according to claim 2 or 3, characterized in that: The phase transition point ranges from 980 to 990°C.

5. The high-strength and high-toughness titanium alloy heat treatment method according to claim 4, characterized in that: The sintered titanium alloy blank is placed in a furnace at a temperature 40°C below its phase transition point and kept warm for 1 to 2 hours, and then water-cooled to room temperature to obtain a first-grade heat-treated titanium alloy.

6. A method for preparing a high-strength and high-toughness titanium alloy, characterized in that: Used to prepare a high-strength and high-toughness titanium alloy as described in claim 1, including the high-strength and high-toughness titanium alloy heat treatment method as described in any one of claims 2 to 5.

7. The method for preparing a high-strength and high-toughness titanium alloy according to claim 6, characterized in that: Before implementing the high-strength and high-toughness titanium alloy heat treatment method according to any one of claims 2 to 5, the preparation method further comprises the following steps: Powder mixing: weighing titanium alloy raw materials according to the mass ratio, mixing the titanium alloy raw materials and then drying them to obtain dried titanium alloy raw materials; Pre-diffusion: placing the dried titanium alloy raw material in a vacuum environment for pre-diffusion to obtain a pre-diffused titanium alloy raw material; Cold pressing a blank: cold pressing the pre-diffused titanium alloy raw material into a blank to obtain a titanium alloy blank; Vacuum sintering: sintering the titanium alloy blank in a vacuum environment to obtain a sintered titanium alloy blank.

8. The method for preparing a high-strength and high-toughness titanium alloy according to claim 7, characterized in that: The powder mixing specifically includes: weighing titanium alloy raw materials according to the mass ratio, using a three-dimensional motion powder mixer to fully mix the titanium alloy raw materials for 1 to 2 hours, and then putting them into a vacuum oven and drying them at 140 to 160° C. for 3 to 5 hours to obtain a dried titanium alloy raw material.

9. The method for preparing a high-strength and high-toughness titanium alloy according to claim 7, characterized in that: The pre-diffusion specifically includes: placing the dried titanium alloy raw material in a vacuum of 1×10 -3 In a vacuum environment below Pa, pre-diffusion is carried out at 700-750° C. for 20-30 minutes to obtain a pre-diffused titanium alloy raw material.

10. The method for preparing a high-strength and high-toughness titanium alloy according to claim 7, characterized in that: The cold pressing of the blank specifically comprises: cold pressing the pre-diffused titanium alloy raw material at a pressure of 240-260 MPa for 8-15 minutes to obtain a titanium alloy blank.

11. The method for preparing a high-strength and high-toughness titanium alloy according to claim 7, characterized in that: The vacuum sintering specifically includes: sintering the titanium alloy blank in a vacuum environment with a vacuum degree of 1×10 -3 Pa, the temperature is 1150-1250°C, the sintering time is 3-6h, and the heating rate is 5-20°C / min to obtain a sintered titanium alloy blank.

12. The method for preparing a high-strength and high-toughness titanium alloy according to claim 7, characterized in that: The titanium alloy raw material is prepared by rotary electrode atomization and has a particle size of 100 to 325 meshes.